STRATEGI OPTIMALISASI DIGITAL MARKETING BAGI KLINIK MAWAR SIMO SUNGELEBAK LAMONGAN - Darojat, Amalia Alfi Karromallahu (J-MACC : journal of management and accounting, 2023)
A Digital media is a marketing communication that has been implemented in several companies that produce goods and also health services, including clinics. This research aims to explain how to market the clinic by utilizing digital media. The research method was by means of a literature review from the Science Direct database., ProQuest and SpringerLink. Articles were selected according to the exclusion and inclusion criteria. A total of 3 articles were filtered from 2,100 articles and then a literature review was carried out. The results of the Mawar Clinic research need to carry out effective and efficient digital marketing, in order to promote medical care services in expanding clinical business marketing while continuing to provide quality care services. Social media as a digital marketing platform that is in great demand by patients. The use of digital marketing can be applied to the marketing of Health Clinic service products and can strengthen the brand image of owned health facilities. Digital marketing can be through applications designed by the clinic personally or other models. Social media platforms can be increased by the highest participation from the patient's side. Supervision and monitoring as well as consistent commitment from the clinic can improve service quality.